Designing a Game To Introduce and Educate Computational Thinking - Millen Dhita; Erdhi Widyarto Nugroho; T. Brenda Chandrawati (SISFORMA, 2024)
To prepare for the industrial era 4.0, the education system in Indonesia needs to change, from only providing learning materials to learning that involves students' ability to think creatively. One way to change this learning system is to implement other learning techniques that hone one's ability to be able to think creatively in solving a problem. One of these learning techniques is Computational Thinking or commonly abbreviated as CT. In Indonesia, Computational Thinking techniques have not been widely used in the teaching and learning process, therefore this research is intended to introduce Computational Thinking learning techniques through game media."Take Me Home" is the name of the game developed to support this research, "Take Me Home" is a serious game created to hone and introduce players to Computational Thinking learning techniques, the game "Take Me Home" is made attractive as possible so that players want to play it continuously by using a procedurally generated map players will always get a different form of game level every time they play the game "Take Me Home", having an Endless level also makes players feel challenged to keep playing.With "Take Me Home" it is hoped that players will learn how to solve problems using creative thinking and also get to know Computational Thinking techniques by designing games that are easy, interesting and educational researchers can also see whether the game "Take Me Home" will continue to be useful and players want to play “Take Me Home” in the future.